Facilitating and supporting the engagement of patients, families and caregivers in research: the “Ottawa model” for patient engagement in research - Shelley Vanderhout; Stuart Nicholls; Zarah Monfaredi; Claudia Hampel; Lynn Ashdown; Maxime Bilodeau; Susan Rich; Beverley Shea; Dean Fergusson (Research Involvement and Engagement, 2022)
Plain English summary Involving patients and families as partners in planning, conducting, and sharing results of health research, referred to as patient engagement, is becoming more common and recognized as important part of the research process. However, guidelines and examples of how to do this well are limited. In this article, we describe the development and features of the Ottawa Patient Engagement in Research Model at The Ottawa Hospital (TOH) and the Ottawa Hospital Research Institute (OHRI). Key pieces of the model include: a Patient and Family Engagement Program, which recruits, educates, and supports patients and families to engage in clinical care, decision making, and research; the Ottawa Methods Centre, which leads studies to understand the best methods to conduct research, and provides support to researchers for patient engagement; and the Office of Patient Engagement in Research Activities, which connects patients, researchers, clinicians, and other stakeholders. Early success of this model may be a result of shared priorities between TOH, OHRI and patients, the creation of a patient engagement policy, ongoing support provided to patients, family members and researchers, and creative methods for recruitment, tracking and evaluation procedures. Ongoing challenges and next steps include promoting diversity among patient partners, setting up a fair and transparent policy for compensating patient partners, and engaging patients across a variety of roles and research areas. This model represents a unique effort of patients, clinicians, researchers, and policymakers across disciplines and institutions to produce one strategy for meaningful teamwork with patients and families in health research.